Social behaviour in farm animals - Keeling, L. J. (Linda J.); Gonyou, H. W. (Harold W.) (CABI Pub., 2001)
The book is about social behaviour in farm animals (cattle, pigs, domestic birds, sheep, horses and fish). Part I of the book deals with the concepts of social behaviour, Part II concentrates on species-specific animal behaviour, and part III tackles the contemporary topics in social behaviour.